Treatment of a large osseous defect in a feline tarsus using a stem cell‐seeded custom implant. (23rd July 2020) - Fitzpatrick, Noel; Black, Cameron; Choucroun, Melissa; Blunn, Gordon; Meswania, Jay; Sanghani‐Kerai, Anita
Abstract: The aim of this study is to describe the treatment of an infected segmental bone defect in a cat using a novel, custom‐designed titanium implant seeded with adipose‐derived stem cells (AdMSCs) to facilitate osseous ingrowth and preserve limb function. Large bone defects occur secondary to trauma, infection, or neoplasia and often result in amputation. We established a novel autologous AdMSC‐impregnated trabecular metal spacer made using 3D printing, to bridge the distal tibia and metatarsal bones in the left pelvic limb of a cat that had previously undergone right pelvic limb amputation. Six months postoperatively, there was radiographic evidence of bone growth and implant integration. A titanium spacer seeded with AdMSCs successfully encouraged bone ingrowth in a large defect site and successfully preserved limb function. However, further studies are needed to justify the use of differentiated stem cell impregnated mesh as a framework to bridge large bone defects.